Dictionaries and ideologies: some remarks of the EFL lexicography - Włodarczyk-Stachurska, Anna (Journal of Education Culture and Society, 2020)
The term ideology itself has recently gained a lot of attention in anthropology, sociolinguistics and cultural studies. As a starting point it seems crucial to form an area of inquiry, that is the sense of language ideology. Here Alan Rumsay’s (1990, p. 346) definition is a useful starting point: „[…] linguistic ideologies are shared bodies of commonsense notions about the nature of language in the world”. The article aims to look at the way EFL dictionaries cope with the task to present the standardization of certain words and usages. In other words, we will attempt to find out if/how lexicographers cope with the job of being legislators, if their products advise about the proper usage as well as meanings of the words available in the standard forms of English. In order to achieve this goal, the number of issues of paramount importance will be investigated:• The term of linguistic ideology,• The concept of standardization• The dictionaries and ideology of standard – the state of the art Our method is making comparisons between different lexicographic sources (dictionaries) in relation to selected entries, and generalising from the way the latter are presented (in the sense of formal and semantic values).